Role of Gender in Shaping Consumer Responses to Doctor Influencer: Insights into Brand Perceptions and Repurchase Intentions in the Indonesian Mineral Water Industry - Endang Dwi Amperawati; Rahmawati Rahmawati; Endang Hariningsih; Wing Wahyu Winarno; Diana Airawaty; Agus Dwianto (Qubahan Academic Journal)
This study investigates the effectiveness of influencer marketing, focusing on Dr. Reisa's endorsement of Le Minerale mineral water in Indonesia. It examines how influencer attributes, such as physical attractiveness, familiarity, expertise, success appeal, and congruency, influence consumer attitudes and repurchase intentions. This study examined the impact of influencer marketing on brand perception and consumer behavior, particularly in the digital era. It challenges traditional marketing theories by analyzing the role of various influencer attributes in shaping consumer attitudes. The primary aim of this study is to assess the unique effects of influencer characteristics on brand attitudes and repurchase intentions, with a special focus on the role of gender as a moderating variable in influencer marketing. This study utilized a survey-based approach to evaluate the impact of influencer attributes—physical attractiveness, familiarity, expertise, success appeal, and congruency on consumer attitudes and repurchase intentions toward Le Minerale’s mineral water. Targeting consumers familiar with Dr. Reisa's endorsement, the survey collects quantitative data to analyze how these attributes, along with gender as a moderating variable, influence brand perception in the digital marketing context. This study reveals that Dr. Reisa's physical attractiveness does not significantly impact brand attitudes, challenging traditional marketing beliefs. However, gender has emerged as a key moderator influencing how attractiveness affects brand perception. Contrary to expectations, familiarity with the influencer has no significant effect on brand attitudes, suggesting a shift in digital audience engagement. Notably, expertise, success appeal, and congruency significantly influence brand attitudes, with gender enhancing the impact of congruency. These insights offer a new perspective on influencer marketing, emphasizing the importance of expertise, success appeal, congruency, and gender considerations, thereby providing marketers with strategic guidance in the digital landscape.